Penerapan Yoga Dalam Upaya Mengurangi Kecemasan Pada Lansia di Panti Wreda Budi Dharma Kasih Purbalingga - Wahyuni, Sri; Sukmaningtyas, Wilis; Nur Ardiyani, Fauziah Hanum (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Elderly is the stage of old age in the development of men and women aged 60 years and over. As a person gets older, their physical abilities decrease so that their social role is reduced, their essential needs are disturbed and anxiety arises. This community service (PkM) activity aims to provide education and apply yoga exercises to reduce anxiety in the elderly. This PkM method is carried out by providing material using power points about anxiety and the benefits of yoga for the elderly and carrying out yoga therapy according to the SOP using video media about elderly yoga exercises. Yoga is done 3 times, namely on Monday, Wednesday and Friday with a duration of 20 minutes. , then assess the level of knowledge and anxiety level pre-implementation and post-implementation of presentation of material and yoga therapy by conducting an evaluation using the HRS-A questionnaire instrument and knowledge level questionnaire. The average value of the level of knowledge before education was in the highest category, namely Sufficient as many as 15 participants or (83.3%) after education increased to the good category as many as 3 participants or (83.3%) and the average value of anxiety before implementing yoga was 50.0% and after applying yoga the average anxiety level was 38.89%. There is a difference in the amount of decline between pre and post of 11.11%. From the results of Community Service it can be concluded that there is an increase in knowledge and a decrease in anxiety. The expected output from this PkM activity is that the elderly can apply yoga in an effort to reduce anxiety, a video containing yoga therapy for the elderly, and the publication of community service articles.